2011
DOI: 10.1371/journal.pone.0025442
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 Receptor Antagonist Modulates the Early Phase of Liver Regeneration after Partial Hepatectomy in Mice

Abstract: BackgroundCytokine administration is a potential therapy for acute liver failure by reducing inflammatory responses and favour hepatocyte regeneration. The aim of this study was to evaluate the role of interleukin-1 receptor antagonist (IL-1ra) during liver regeneration and to study the effect of a recombinant human IL-1ra on liver regeneration.MethodsWe performed 70%-hepatectomy in wild type (WT) mice, IL-1ra knock-out (KO) mice and in WT mice treated by anakinra. We analyzed liver regeneration at regular int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 55 publications
4
35
0
1
Order By: Relevance
“…Our data showed a protective effect of IL-1Ra in the development of ALD. A protective effect of the blockade of IL-1 signaling has also been shown in TLR9-associated liver injury (14), recovery after partial hepatectomy in mice (36), and liver failure induced by d-galactosamine (37). Moreover, we demonstrated, for the first time to our knowledge, that administration of IL-1Ra inhibited progression of already established ALD and facilitated recovery from acute-on-chronic alcoholic liver injury, a scenario observed in the majority of patients presenting with acute alcoholic hepatitis (1).…”
Section: Figure 10mentioning
confidence: 90%
“…Our data showed a protective effect of IL-1Ra in the development of ALD. A protective effect of the blockade of IL-1 signaling has also been shown in TLR9-associated liver injury (14), recovery after partial hepatectomy in mice (36), and liver failure induced by d-galactosamine (37). Moreover, we demonstrated, for the first time to our knowledge, that administration of IL-1Ra inhibited progression of already established ALD and facilitated recovery from acute-on-chronic alcoholic liver injury, a scenario observed in the majority of patients presenting with acute alcoholic hepatitis (1).…”
Section: Figure 10mentioning
confidence: 90%
“…Recent studies have shown that FHF is an inflammatory disease; this conclusion is supported clinically by elevated serum levels of immuno-inflammatory cytokines, including IL-1, TNF, IL-6 [7], and IL-8 [8]. Uncontrolled hepatic immunoactivation is regarded as the primary pathological mechanism of FHF [9].…”
Section: Introductionmentioning
confidence: 99%
“…Поскольку воспалительная реакция яв-ляется триггером и поддерживает развитие фи-броза, значительный интерес в лечении ЦП отво-дится противовоспалительным стратегиям [41]. Действительно, подавление воспаления благо-приятствует регенерации печени при острой пе-ченочной недостаточности [47,57] и позитивно сказывается на функциях печени при тяжелых формах алкогольной болезни [7,52].…”
Section: Discussionunclassified